CHEMICAL CONSTITUENTS, ANTIOXIDATIVE, CYTOTOXIC, AND GENOTOXIC EFFECTS OF MISCANTHUS CAPENSIS ROOTS EXTRACT: Chemical Constituents, Anti-Oxidative, Cytotoxic and Genotoxic Effects of Miscathus Capensis Roots Extract. - IDOWU JONAS SAGBO; WILFRED OTANG MBENG (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Miscanthus capensis (Nees) Andersson (Poaceae family) is used in traditional medicine to treat pimples, wounds, eczema, acne, and other ailments. The present study investigates the possible chemical constituents, antioxidant, cytotoxic, and genotoxic effects of the methanol extract of the M. capensis roots. Methods: Gas chromatography-mass spectrometry (GC-MS) analysis was carried out to identify the chemical constituents of the plant extract. Cytotoxicity and mode of cell death toward human dermal fibroblasts (MRHF) cells were assessed using the ImageXpress® Micro XLS analysis system. Genotoxic effect toward Vero cells was also investigated using micronucleus assay. Furthermore, ferric reducing power (Ferric reducing antioxidant potential [FRAP]) and reactive oxygen species (ROS) levels in MRHF cells were used to estimate the antioxidant activity of the plant extract. Results: The GC-MS results showed a maximum amount of bioactive components (77 compounds) with rosifoliol (33.66%) being the major component detected. However, the extract was not toxic to MRHF cells but demonstrated anti-proliferation rather than cell death at the tested concentrations (25, 50, and 100 μg/ml). In addition, the plant extract also displayed non-genotoxic toward Vero cells with no significant increase in micronucleus formation at the tested concentration while a concentration dependence response in FRAP values and ROS levels in MRHF cells lines were observed indicating better antioxidant activities of the plant extract. Conclusion: The results suggest that M. capensis could be a promising candidate for preventing or eradicating skin and oxidative-stress related diseases.